2020
DOI: 10.1016/j.onehlt.2020.100186
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E in Sub Saharan Africa – A significant emerging disease

Abstract: Hepatitis E is an emerging endemic disease found across the African continent, but there are clear differences in epidemiology between North Africa and countries south of the Sahara. In this systematic review, Google scholar and PubMed databases were searched for peer-reviewed articles on HEV epidemiology. Publications meeting our inclusion criteria were critically reviewed to extract consistent findings and identify knowledge gaps. Hepatitis E has been reported in 25 of the 49 countries in Sub Saharan Africa.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 138 publications
(160 reference statements)
1
25
0
Order By: Relevance
“…These different studies show that HEV infections are endemic in the country and that the prevalence of infections can vary depending on the year, the types of patients studied, and the study sites. Other similar studies have shown that HEV IgM seroprevalence is generally between 0-34% in sub-Saharan Africa [17]. The HEV IgM rates detected in other endemic countries were 2.6% in Burkina Faso [18], 10.4% in the Demographic Republic of Congo [12], 38.4% in Niger [19], 22% in Cameroon [20], 0.34% in Algeria [21], and 4.4% in Sudan [22].…”
Section: Discussionmentioning
confidence: 68%
“…These different studies show that HEV infections are endemic in the country and that the prevalence of infections can vary depending on the year, the types of patients studied, and the study sites. Other similar studies have shown that HEV IgM seroprevalence is generally between 0-34% in sub-Saharan Africa [17]. The HEV IgM rates detected in other endemic countries were 2.6% in Burkina Faso [18], 10.4% in the Demographic Republic of Congo [12], 38.4% in Niger [19], 22% in Cameroon [20], 0.34% in Algeria [21], and 4.4% in Sudan [22].…”
Section: Discussionmentioning
confidence: 68%
“…It is a serious public health disease in many developing countries, especially in regions of high faecal contamination of drinking water supplies and poor sanitation [ 3 ]. As a neglected tropical disease related to water, sanitation, and hygiene (WASH), HEV infection has a huge burden on many underprivileged populations in developing countries but has gained insufficient attention in terms of control interventions, research, and treatment options [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…On literature review, rare cases of co-infection with Plasmodium and HEV have been reported with an abysmal prognosis. For interest and awareness, we report an unusual case of a co-infection of hepatitis E in a patient who developed cerebral malaria from Plasmodium falciparum infection [ 10 ].…”
Section: Introductionmentioning
confidence: 99%